Data Trends in Industry Automation Using .NET Framework. Issue 4 (2015) - Mikolajek, M.; Otevrel, V.; Koziorek, J.; Slanina, Z.
Abstract: This paper is focused on design and implementation of universal data interface for historical and real trends viewer analyzer in industry automation using. The first parts of paper are focused on usual situations with data interface in industry automation and data viewers. These parts exactly summarized actual situation about problematic of trends in industry automation. Next parts of paper are focused on research and implementation data interface in C# programming language as dynamic link library (DLL). Designed data interface allows basic configuration for all data sources. For example - choose data sources, selectable count signals or signal sample steps. The data interface was creating universally so that data interface can be easily edited. The result solution of data interface was tested in developed trend viewer.